Structural Gaps in Regional Infrastructure Financing: an Analysis of Horizontal Coordination Barriers and an Alternative Framework of Vertical Aggregation - Sabilillah Ardie (PT. Anagata Sembagi Education, 2026)
This study examines the feasibility of the Build-to-Lease (BTL) model within the framework of Indonesia's PPP for regional infrastructure financing, as well as formulates the principle of regulatory reform if the model cannot be implemented. With a descriptive-comparative quantitative approach using secondary data from the Ministry of Finance's DJPK, Bappenas PPP Book, SPAM Tuk Jambe project documents, and PPP regulations, as well as a survey of 35 PPP experts, the study found that the structural gap was very high with an Implementation Gap Index (IGI) of 86.6%, consisting of Fiscal Gap (86%), Scale Gap (93%), Coordination Gap (100%), and Regulatory Gap (67.5%). An analysis of the content of the Regulation of the Minister of National Development Planning/Head of Bappenas Number 9 of 2025 shows that the BTL model cannot be applied under the current PPP regulations. The Tuk Jambe case is reframed as an illustration of BTL's counterfactual, where horizontal coordination is not the root of the problem but a consequence of the conditions of ownership consolidation. Empirical Discounted Cash Flow (DCF) simulation proves that vertical aggregation through SOEs is an absolute prerequisite for financial feasibility. The research formulated three principles of directional reform: the expansion of the definition of Availability Payment (multi-party), the timing of asset transfers at the beginning, and the easing of sectoral requirements for SOEs as PJPK.